Usefulness of genetic characterization of narcolepsy and hypersomnia on phenotype definition: a study in Portuguese patients - Martins-da-Silva, A (2014)
[ENG] Introduction. The determination of human leukocyte antigen (HLA) class II genotype is widely used to confirm the diagnosis of narcolepsy with or without cataplexy. The HLA genotyping is reliable, easy to perform and reassures the clinician. It is also less invasive than other methodologies and is in accordance with the autoimmune hypothesis for the origin of narcolepsy. Aim. To assess the usefulness of genetic markers (HLA) in the differential diagnosis between different sleep disorders and their relevance in the context of our population. Subjects and methods. We analyzed a cohort of 113 patients with episodes of daytime sleepiness, 38 patients were classified as narcolepsy with cataplexy, 13 as narcolepsy and 62 as hypersomnia/idiopathic hypersomnia. A control population of 206 reportedly healthy individuals from the same geographic origin was used. Results. The HLA-DQB1*06:02 allele frequency was overrepresented in patients with narcolepsy and narcolepsy with cataplexy (46% and 71% respectively vs. 16% in control population), with a value of p = 4.53–13 for narcolepsy with cataplexy. The HLA-DQB1*02 frequency was increased in the population with hypersomnia when compared with the control population (55% vs. 34%; p = 0.004). Conclusions. Genetic characterization has the potential to enhance the ability to carry out differential diagnosis among diverse excessive daytime sleepiness phenotypes, corresponding to diverse entities with different biological mechanisms